2011
DOI: 10.1074/jbc.m110.213660
|View full text |Cite
|
Sign up to set email alerts
|

CIN85 Modulates the Down-regulation of FcγRIIa Expression and Function by c-Cbl in a PKC-dependent Manner in Human Neutrophils

Abstract: We previously described a non-classical mechanism that arrests Fc␥RIIa signaling in human neutrophils once engaged by immune complexes or opsonized pathogens. The engagement of Fc␥RIIa leads to its ubiquitination by the ubiquitin ligase c-Cbl and degradation by the proteasome. Herein, we further examined some of the events regulating this novel pathway. The adaptor protein CIN85 was described in other systems to be involved in the regulation of the c-Cbl-dependent pathway. We found that CIN85 is expressed in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 64 publications
(84 reference statements)
1
19
0
1
Order By: Relevance
“…The effect of drugs (0-4 h treatments) on autophagic signaling was tested in PMNLs maintained in DMEM + 10% FBS (8 × 10 6 cells per 25-cm 2 flasks). After treatment, the cells were centrifuged, washed in HBSS, respun, resuspended in sample buffer and boiled as described (Marois et al, 2011). Cells extracts equivalent to 1.6 × 10 6 cells per lane were run on 12% SDS-PAGE and transferred to PVDF membranes.…”
Section: Cellsmentioning
confidence: 99%
“…The effect of drugs (0-4 h treatments) on autophagic signaling was tested in PMNLs maintained in DMEM + 10% FBS (8 × 10 6 cells per 25-cm 2 flasks). After treatment, the cells were centrifuged, washed in HBSS, respun, resuspended in sample buffer and boiled as described (Marois et al, 2011). Cells extracts equivalent to 1.6 × 10 6 cells per lane were run on 12% SDS-PAGE and transferred to PVDF membranes.…”
Section: Cellsmentioning
confidence: 99%
“…For this, we made use of heat-aggregated (HA)-IgG, a well-accepted immune complex surrogate. 48 Considering that previous studies indicated that FcgRIIA cross-linking induces platelet activation, including arachidonic acid metabolism, 49 we have analyzed the expression of surface markers and MP formation. Our results indicate that incubation of platelets with monomeric IgG did not activate platelets (used as control), whereas HA-IgG induced platelet surface For personal use only.…”
Section: Virus-mediated Platelet Activation 2855mentioning
confidence: 99%
“…21 A recent study showed that CIN85 modulates c-Cbl-mediated down-regulation of Fc␥RIIa in human neutrophils. 22 It is thus of interest to determine whether CIN85 regulates the signaling pathways of other multimeric immune receptors, such as the T-and B-cell receptors.…”
Section: Introductionmentioning
confidence: 99%
“…21 A recent study showed that CIN85 modulates c-Cbl-mediated down-regulation of Fc␥RIIa in human neutrophils. 22 It is thus of interest to determine whether CIN85 regulates the signaling pathways of other multimeric immune receptors, such as the T-and B-cell receptors.Here, we demonstrate that CIN85 is constitutively associated with c-Cbl, Cbl-b, and BLNK in human B cells. Gain-of-function and loss-of-function experiments revealed that CIN85 up-regulated c-Cbl phosphorylation and inhibited BCR-induced calcium flux and phosphorylation of Syk and PLC␥2, without affecting BCR internalization.…”
mentioning
confidence: 99%